Genetic diversity and candidate gene association analysis for growth in the South African Yellowtail (Seriola lalandi) - Jansen van Rensburg, Mieke (Stellenbosch : Stellenbosch University, 2026)
Thesis (MSc)--Stellenbosch University, 2026.